Evaluating the impact of AI debater on EFL debate competence: Perceptions of lecturers and learners - Ranta Butarbutar; Andi Haeriati Alimuddin; Seli Marlina Radja Leba (Universitas Syiah Kuala, 2025)
Debate competence is essential in English as a Foreign Language (EFL) learning, yet many learners struggle with critical thinking, argumentation, and persuasive communication. While artificial intelligence (AI) offers promising support, evidence of its effectiveness in debate learning remains scarce. This study aims to evaluate the impact of AI Debater technology on the debate performance of EFL learners and explore the perceptions of its use among lecturers and learners. A quasi-experimental design was employed, involving 20 EFL learners and one lecturer, with data collected through observations and online interviews. Post-test results showed significant improvements in debate performance, with mean scores of 77.45 for content, 78.75 for arguments, and 79.35 for claims. Learners also reported positive perceptions: 85% rated the AI Debater as very useful, while 80% and 75% valued its role in developing claims and arguments, and 90% evaluated content positively; however, only 50% found it highly effective for collaboration. Complementing these findings, lecturers perceptions emphasized three areas: (1) reasons for choosing the AI Debater, such as accessibility, up-to-date information, suitability for 21st-century learners, and time efficiency, (2) its impact, including improved critical thinking, reasoning, negotiation, analytical skills, and persuasive communication, and (3) challenges, such as reliability issues, lack of creativity and empathy, and concerns about educational integrity. While AI Debater shows potential for enhancing debate skills, the absence of a control group, small sample size, and limited consideration of contextual factors constrain findings. Future research should address these gaps to deepen the understanding of AI in EFL debate learning.